MORPHOFUNCTIONAL CHARACTERISTICS OF MESENTERIC LYMPH NODES IN THE COMBINED EFFECT OF HYPOXIA AND INFECTION - Yagubova, S.M.; Mirzayeva, T.N.; Sultanova, T.S.; Akbarov, E.Ch.; Farzaliyeva, S.A.; Ibishova, A.V. (World of Medicine and Biology, 2025)
The article presents information on the study conducted, the purpose of which was a comprehensive study of morphofunctional changes in the mesenteric lymph nodes under the combined effects of hypoxia and infection, as well as compensatory-adaptive processes formed in the lymphoid tissue. The study was conducted on mesenteric lymph nodes of white rats weighing 180–200 grams, using histological, electron microscopic, and morphometric methods. On the 15th day of the study, acute destruction and necrosis of cells, a significant decrease in morphometric parameters, vacuolization of most organelles were observed. At a later stage of the study (day 30), depletion and atrophy of follicles, as well as, conversely, an increase in connective tissue were revealed. These findings suggest pathological remodeling of the lymph nodes, reflecting both a structural response and an adaptive reaction to the combined effects of hypoxia and infection.
Keywords: hypoxia; infection; mesenteric lymph nodes